Melatonin, A Promising Therapeutic for Diabetes Mellitus and Its Complications: A Narrative Review - Yanuarita Tursinawati; Arum Kartikadewi; Ari Yuniastuti; R Susanti (Journal of Biomedicine and Translational Research, 2021)
Diabetes mellitus (DM) is a non-communicable disease and still a health problem in the world. Melatonin is responsible to metabolize carbohydrate and regulate blood sugar levels. Several studies proved Melatonin is useful in the diabetes therapy and its complication by performing antioxidant activity through various signaling pathways. The role of the melatonin hormone in the pathogenesis of complications of diabetes mellitus is still a lot of controversy. Animal studies are still incomplete to explain the mechanism of action of melatonin. Therefore, this review aims to discuss Melatonin role administration in DM and its complications. This review was started by searching articles using electronic databases such as Google Scholar, Science Direct, SpringerLink and Pubmed between 2009-2019. Melatonin increased respiration within mitochondria; acted as antioxidant that fight free radical production; and reduced oxidative stress. It diminished proinflammatory cytokines in diabetes and prevents various DM complications on eyes, cardiac and male reproductive organs through antioxidant effects. It inhibited proinflammatory within several signaling Pathways, included PI3K/Akt-Nrf2,cGMP-PKG, Nrf-2-HO-1 and MAPK, Syk, p38MAPK pathways. There are various melatonin roles in diabetes and DM complications as a promising new breakthrough of DM treatment. It is necessary to explore Melatonin role in other DM complications. Most of this research is on experimental animals, thus clinical trial studies should be carried out in humans to make melatonin a promising therapeutic or prevention for diabetes and its complications in the future